PTU-240 Improving outcomes of endoscopic retrograde cholangio-pancreatography with the use of new techniques in a district general hospital setting. (28th May 2012) - Owen, N; Macfarlane, B; King, A; Leahy, A
Abstract : Introduction: Outcomes of endoscopic retrograde cholangio-pancreatography (ERCP) performed at West Hertfordshire Hospital NHS Trust (WHHT) in 2007 and 2011 were compared. The 2011 data followed introduction of the techniques of wire-guided cannulation and balloon sphincteroplasty. Outcomes measured included successful biliary cannulation on first ever ERCP, the use of precut, successful stenting of strictures, stone extraction and post ERCP pancreatitis rates. The number of referrals to a tertiary centre due to failed ERCP in both years was also calculated. The outcomes were compared with national data from the BSG ERCP audit of 2007. 1 Methods: Local data were obtained from all ERCP performed at WHHT in the years 2007 and 2011. Success of cannulation, precut use, successful stenting and stone extraction was collected from electronic ERCP reports. Post ERCP pancreatitis rates were obtained by confirming hyperamylasaemia post ERCP of at least three times the upper limit of normal requiring admission to hospital or prolongation of planned admission of ≥2 nights, as per the BSG 2007 Audit definitions. 1 Similar national outcomes were taken from the BSG 2007 Audit. 1 Results: Results are summarised below: A Fisher's exact test was performed to compare data. A statistically significant difference was found between the 2007 and 2011 groups (p value <0.01) when comparing successful stone extraction. Tertiary centre referrals due to failed ERCP fell from 12 in 2007 to 4 in 2011. Conclusion: The introduction of wire-guided cannulation has maintained high success rates of biliary cannulation with a reduction in post ERCP pancreatitis, as observed in previous studies. 2 Following adopting the technique of balloon sphincteroplasty there has been a statistically significant improvement in the success of stone extraction. A subsequent reduction in referrals to tertiary centres for failed ERCP has also been observed. Competing interests: None declared. References: 1. Williams EJ, Taylor S, Fairclough P, et al. Are we meeting the standards set for endoscopy? Results of a large-scale prospective survey of endoscopic retrograde cholangio-pancreatograph practice. Gut 2007;56 :821–9. 2. Artifon EL, Sakai P, Cunha JE, et al. Guidewire cannulation reduces risk of post-ERCP pancreatitis and facilitates bile duct cannulation. Am J Gastroenterol 2007;102 :2147–53.